The Contribution of the Biota Diversity of Lake Toba to Indonesia's Biota Wealth - Ika Rosenta Purba; Nurhayati Nurhayati (Postgraduate, University of Mataram, 2024)
This study aims to analyze the contribution of the diversity of biota in the waters of Toba Lake to the richness of Indonesia's biota. Research is needed to analyze the diversity of Lake Toba water biota. In order to achieve this goal, data and information collected regarding the contribution of the diversity of Lake Toba waters to the richness of Indonesia's biota is used. Verification of the data and information obtained was carried out through literature study, document analysis, interviews and filling out questionnaires. The results showed that in the waters of the lake there are endemic fish species whose existence is currently almost extinct, namely Batak fish or